Revealing the pH‐Dependent Photoluminescence Mechanism of Graphitic C3N4 Quantum Dots. Issue 9 (17th July 2019) - Zhou, Zhaobo; Niu, Xianghong; Ma, Liang; Wang, Jinlan
Abstract: Graphitic C3 N4 quantum dots (g‐C3 N4 QDs), as a kind of widely explored fluorescent materials, show pH‐dependent photoluminescence feature. However, opposite variation tendencies on their pH‐dependent photoluminescence performance are observed in different experiments and the underlying mechanism remains unclear. Herein, based on time‐dependent density functional theory and nonadiabatic molecular dynamics simulations, a synergistic mechanism between light absorption and radiative/nonradiative recombination of g‐C3 N4 QDs in neutral and acidic conditions is proposed to address the inconformity. Specifically, under weak acidic condition, the strong light absorption and weak nonradiative recombination of g‐C3 N4 QDs yield strong fluorescence emission. While under strong acidic condition, although the light absorption remains high, the fast nonradiative electron‐hole recombination dramatically reduces the population of the excited state and the fluorescence is quenched consequently. The protonation of N atom changes the orbital composition of transition channels and frontier molecular orbital overlap, which consequently modulates the competition between radiative and nonradiative recombination as well as the emission performance. In addition, there is no obvious change in the variation tendency of absorption and emission properties of g‐C3 N4 QDs with different functional groups, implying the general applicability of understanding. Abstract : A synergistic mechanism between light absorption and radiative/nonradiative recombination is proposed to address the inconformity of graphitic C3 N4 quantum dots (g‐C3 N4 QDs) in neutral and acidic conditions. In addition, there is no obvious change in the variation tendency of absorption and emission properties of g‐C3 N4 QDs with different functional groups.